Mortality, functional outcome, and bleeding risk after early versus delayed thrombectomy - Zoltan Ungvari; János Tibor Fekete; Mónika Fekete; Andrea Lehoczki; Rafal Gulej; Farzaneh Sorond; Eric Liotta; Calin I. Prodan; Peter Toth; Csaba Kiss; Anna Ungvari; Balázs Győrffy (GeroScience, 2025)
Endovascular thrombectomy (EVT) is an established treatment for acute ischemic stroke, due to large vessel occlusion (LVO), but the optimal time window for intervention remains a subject of ongoing debate. We aimed to assess the impact of treatment timing on mortality, functional outcomes, and safety by comparing early (≤ 6 h) versus late (> 6–24 h) EVT. We conducted a systematic review and meta-analysis to evaluate the effect of time to intervention on outcomes of endovascular thrombectomy (EVT) in acute ischemic stroke. Four databases (PubMed, Web of Science, Cochrane Library, and EMBASE) were searched for studies published between 2000 and 2024. Eligible randomized controlled trials and cohort studies reported on 90-day mortality, functional outcome (modified Rankin Scale, mRS), or symptomatic intracranial hemorrhage (sICH), stratified by treatment timing (≤ 6 h vs. > 6–24 h from symptom onset). Pooled incidence rates, incidence rate differences (IRD), and incidence rate ratios (IRR) were calculated using random-effects models. Eighteen studies met inclusion criteria. The pooled incidence of symptomatic intracranial hemorrhage (sICH) was 0.19 events per person-year (95% CI: 0.12–0.26) in the early group and 0.23 events per person-year (95% CI: 0.11–0.35) in the late group, with no significant difference between groups (incidence rate difference [IRD] − 0.028; p = 0.33, incidence rate ratio [IRR] 0.88; p = 0.33). For mortality, early EVT showed a significantly lower incidence rate of 0.66 events per person-year (95% CI: 0.51–0.82) compared to 0.77 events per person-year (95% CI: 0.63–0.91) in the late EVT group (IRD − 0.148; p = 0.0012, IRR 0.81; p = 0.0014). Functional independence was more frequent in the early group (1.72; 95% CI: 1.42–2.01) than in the late group (1.45; 95% CI: 0.91–1.98) (IRD 0.32; p < 0.0001, IRR 1.22; p < 0.0001). Heterogeneity was moderate to high across outcomes. The timing of endovascular thrombectomy significantly influences clinical outcomes in acute ischemic stroke. Our analysis shows that early intervention (within 6 h) is associated with a significantly lower mortality rate and a higher likelihood of achieving functional independence at 90 days compared to late intervention (beyond 6 up to 24 h). The incidence of symptomatic intracranial hemorrhage did not differ significantly between the groups, suggesting that late treatment does not increase safety risks. These findings underscore the importance of minimizing treatment delays, while also supporting the continued use of EVT in selected patients beyond the 6-h window.

Detecting early stages of Alzheimer’s disease using a web-based cognitive battery - Jordan R. Hoffmeister; Brady R. Robison; Christopher T. Copeland; Calin I. Prodan; Jim G. Scott; Jordan M. Glenn (GeroScience, 2024)

Linking peripheral atherosclerosis to blood–brain barrier disruption: elucidating its role as a manifestation of cerebral small vessel disease in vascular cognitive impairment - Ádám Nyúl-Tóth; Roland Patai; Anna Csiszar; Anna Ungvari; Rafal Gulej; Peter Mukli; Andriy Yabluchanskiy; Zoltan Benyo; Peter Sotonyi; Calin I. Prodan; Eric M. Liotta; Peter Toth; et al. (GeroScience, 2024)
Aging plays a pivotal role in the pathogenesis of cerebral small vessel disease (CSVD), contributing to the onset and progression of vascular cognitive impairment and dementia (VCID). In older adults, CSVD often leads to significant pathological outcomes, including blood–brain barrier (BBB) disruption, which in turn triggers neuroinflammation and white matter damage. This damage is frequently observed as white matter hyperintensities (WMHs) in neuroimaging studies. There is mounting evidence that older adults with atherosclerotic vascular diseases, such as peripheral artery disease, ischemic heart disease, and carotid artery stenosis, face a heightened risk of developing CSVD and VCID. This review explores the complex relationship between peripheral atherosclerosis, the pathogenesis of CSVD, and BBB disruption. It explores the continuum of vascular aging, emphasizing the shared pathomechanisms that underlie atherosclerosis in large arteries and BBB disruption in the cerebral microcirculation, exacerbating both CSVD and VCID. By reviewing current evidence, this paper discusses the impact of endothelial dysfunction, cellular senescence, inflammation, and oxidative stress on vascular and neurovascular health. This review aims to enhance understanding of these complex interactions and advocate for integrated approaches to manage vascular health, thereby mitigating the risk and progression of CSVD and VCID.

Atherosclerotic burden and cerebral small vessel disease: exploring the link through microvascular aging and cerebral microhemorrhages - Anna Csiszar; Anna Ungvari; Roland Patai; Rafal Gulej; Andriy Yabluchanskiy; Zoltan Benyo; Illes Kovacs; Peter Sotonyi; Angelia C. Kirkpartrick; Calin I. Prodan; Eric M. Liotta; Xin A. Zhang; et al. (GeroScience, 2024)
Cerebral microhemorrhages (CMHs, also known as cerebral microbleeds) are a critical but frequently underestimated aspect of cerebral small vessel disease (CSVD), bearing substantial clinical consequences. Detectable through sensitive neuroimaging techniques, CMHs reveal an extensive pathological landscape. They are prevalent in the aging population, with multiple CMHs often being observed in a given individual. CMHs are closely associated with accelerated cognitive decline and are increasingly recognized as key contributors to the pathogenesis of vascular cognitive impairment and dementia (VCID) and Alzheimer’s disease (AD). This review paper delves into the hypothesis that atherosclerosis, a prevalent age-related large vessel disease, extends its pathological influence into the cerebral microcirculation, thereby contributing to the development and progression of CSVD, with a specific focus on CMHs. We explore the concept of vascular aging as a continuum, bridging macrovascular pathologies like atherosclerosis with microvascular abnormalities characteristic of CSVD. We posit that the same risk factors precipitating accelerated aging in large vessels (i.e., atherogenesis), primarily through oxidative stress and inflammatory pathways, similarly instigate accelerated microvascular aging. Accelerated microvascular aging leads to increased microvascular fragility, which in turn predisposes to the formation of CMHs. The presence of hypertension and amyloid pathology further intensifies this process. We comprehensively overview the current body of evidence supporting this interconnected vascular hypothesis. Our review includes an examination of epidemiological data, which provides insights into the prevalence and impact of CMHs in the context of atherosclerosis and CSVD. Furthermore, we explore the shared mechanisms between large vessel aging, atherogenesis, microvascular aging, and CSVD, particularly focusing on how these intertwined processes contribute to the genesis of CMHs. By highlighting the role of vascular aging in the pathophysiology of CMHs, this review seeks to enhance the understanding of CSVD and its links to systemic vascular disorders. Our aim is to provide insights that could inform future therapeutic approaches and research directions in the realm of neurovascular health.

Preventing spontaneous cerebral microhemorrhages in aging mice: a novel approach targeting cellular senescence with ABT263/navitoclax - Janet Faakye; Ádám Nyúl-Tóth; Mihaly Muranyi; Rafal Gulej; Boglarka Csik; Santny Shanmugarama; Stefano Tarantini; Sharon Negri; Calin Prodan; Peter Mukli; Andriy Yabluchanskiy; Shannon Conley; et al. (GeroScience, 2023)

Imaging the time course, morphology, neuronal tissue compression, and resolution of cerebral microhemorrhages in mice using intravital two-photon microscopy: insights into arteriolar, capillary, and venular origin - Janet Faakye; Ádám Nyúl-Tóth; Rafal Gulej; Boglarka Csik; Stefano Tarantini; Santny Shanmugarama; Calin Prodan; Peter Mukli; Andriy Yabluchanskiy; Shannon Conley; Peter Toth; Anna Csiszar; et al. (GeroScience, 2023)

Stringent public health measures during COVID-19 across ischemic stroke care systems: the potential impact of patient perceptions on health care-seeking behaviors - Calin I. Prodan; Ayush Batra; Zoltan Ungvari; Eric M. Liotta (GeroScience, 2022)

Applying Quantitative Radiographic Image Markers to Predict Clinical Complications After Aneurysmal Subarachnoid Hemorrhage: A Pilot Study - Gopichandh Danala; Masoom Desai; Bappaditya Ray; Morteza Heidari; Sai Kiran R. Maryada; Calin I. Prodan; Bin Zheng (Annals of Biomedical Engineering, 2022)

Increased procoagulant platelet levels are predictive of death in COVID-19 - Mohamad H. Khattab; Calin I. Prodan; Andrea S. Vincent; Chao Xu; Kellie R. Jones; Sharanjeet Thind; Meheroz Rabadi; Shubhada Mithilesh; Eleanor Mathews; Leslie Guthery; George L. Dale; Angelia C. Kirkpatrick (GeroScience, 2021)

High rates of undiagnosed vascular cognitive impairment among American Indian veterans - Angelia C. Kirkpatrick; Julie A. Stoner; Fabiola Donna-Ferreira; George C. Malatinszky; Leslie D. Guthery; James Scott; Calin I. Prodan (GeroScience, 2019)

Repeated Valsalva maneuvers promote symptomatic manifestations of cerebral microhemorrhages: implications for the pathogenesis of vascular cognitive impairment in older adults - Zoltan Ungvari; Andriy Yabluchanskiy; Stefano Tarantini; Peter Toth; Angelia C. Kirkpatrick; Anna Csiszar; Calin I. Prodan (GeroScience, 2018)

Coated-Platelet Trends Predict Short-Term Clinical OutcomeAfter Subarachnoid Hemorrhage - Bappaditya Ray; Vijay M. Pandav; Eleanor A. Mathews; David M. Thompson; Lance Ford; Lori K. Yearout; Bradley N. Bohnstedt; Shuchi Chaudhary; George L. Dale; Calin I. Prodan (Translational Stroke Research, 2018)